Between Identity and Self-Creation - Critical Philosophy as a Practice of the Self in the Light of Michel Foucault’s Philosophy - Mickiewicz, Adriana Joanna (Sensus Historiae, 2020)
The purpose of this thesis is to analyse Michel Foucault’s attitude towards the notion of identity. At the beginning, the article describes a peculiar paradox of Foucault’s thought: on one hand, the philosopher describes the individual as subjected to the constant actions of the power, which is shaping his or hers identity. On the other hand, through the concept of the aesthetics of existence, Foucault introduces the possibility of individual, conscious self-creation. The relationship between the individual and the society can be established after a closer look at how Foucault understood the critical philosophies.